Comparison of miRNA and mRNA Expression in Sika Deer Testes With Age - Jia, Boyin; Zhang, Linlin; Ma, Fuquan; Wang, Xue; Li, Jianming; Diao, Naichao; Leng, Xue; Shi, Kun; Zeng, Fanli; Zong, Ying; Liu, Fei; Gong, Qinglong; et al. (Frontiers in Veterinary Science, 2022)
To elucidate the complex physiological process of testis development and spermatogenesis in Sika deer, this study evaluated the changes of miRNA and mRNA profiles in the four developmental stages of testis the juvenile (1-year-old), adolescence (3-year-old), adult (5-year-old) and aged (10-year-old) stages. The results showed that total total of 198 mature, 66 novel miRNAs, and 23558 differentially expressed (DE) unigenes were obtained. 14918 (8413 up and 6505 down), 4988 (2453 up and 2535 down), 5681 (2929 up and 2752 down) DE unigenes, as well as 88 (43 up and 45 down), 102 (44 up and 58 down), 54 (18 up and 36 down) DE miRNAs were identified in 3-vs.1-, 5-vs.3- and 10-vs.5-year-old testes, respectively. By integrating miRNA and mRNA expression profiles, we predicted 10790 mRNA-mRNA and 69883 miRNA-mRNA interaction sites. The target genes were enriched by GO and KEGG pathways to obtain DE mRNA (IGF1R, ALKBH5, Piwil, HIF1A, BRDT, etc.) and DE miRNA (miR-140, miR-145, miR-7, miR-26a, etc.), which play an important role in testis development and spermatogenesis. The data show that DE miRNAs could regulate testis developmental and spermatogenesis through signaling pathways, including MAPK signaling pathway, p53 signaling pathway, PI3K-Akt signaling pathway, Hippo signaling pathway, etc. miR-140 was confirmed to directly target mutant IGF1R-3’UTR by the Luciferase reporter assays. This study provides a useful resource for future studies on the role of miRNA regulation in testis development and spermatogenesis.